DETERMINATION OF THE SPECTRAL TYPE AND LUMINOSITY OF THE HOT COMPONENT OF THE ECLIPSING BINARY STAR RZ ERI - Karetnikov, V. G.; Menchenkova, E. V.; Syrov, O. I. (Одеські астрономічні публікації, 2017)
By using the spectra taken at 6m telescope and the methods of two-dimensional spectral classification, the non-ordinarity of the main star in RZ Eri is shown. The presence of the circumstellar gas and of the surface activity of the stars in a binary are suggested.